Radio-based agricultural extension promotes uptake of entrepreneurship in sheep fattening: Evidence from Central Ethiopia - Wamatu, Jane; Ekule, Muluken; Abiso, Tesfaye; Belayneh, Tesfa; Rete, Cherinet; Haile, Aynalem (2025)
The radio-driven initiative has significantly increased awareness and practical application of improved sheep fattening techniques among smallholder farmers in rural Ethiopia. In collaboration with FM radio stations, 3.6 million farmers across 11 local languages were reached in Central and Southwestern Ethiopia. The result was an enhanced 67% uptake of improved sheep fattening practices, with a significant 343% increase in household incomes.